Faith in Action: Examining Religious Responses to 21st Century Socio-Economic Challenges - Setia, Paelani; Truna, Dody S.; Hannah, Neng (UIN Sunan Gunung Djati Bandung, 2025)
In the era of globalization, the complexity of social, economic, and environmental challenges has resulted in the decline of the role of traditional religious institutions, as well as the emergence of secularism and religious pluralism. This study aims to reveal the response of religion to the phenomena of secularization, conflict, and economic inequality in the 21st century with a qualitative approach through literature studies. The results of the study indicate that secularism has become a contemporary issue, with a decline in religious affiliation among the younger generation, especially in Europe; however, projections for 2050 show a resurgence of religious adherents and an important role for religion in society. In addition, increasing religious diversity creates challenges and tensions between communities, but many religions respond by building solidarity through dialogue and peace campaigns. Amidst the increasing economic gap, religions respond by reviewing relevant teachings and principles, such as the simplicity movement that combines spiritual values with ways of earning a living, ethical education in business, and playing an active role in anti-poverty campaigns and other social issues. This paper adds insight into the role of religion in building sustainable social solidarity and economic ethics amidst contemporary challenges.